The Depression Categories of Adolescent with Beta-Thalassemia Major - Wafa Fida Az-zahra; Ai Mardhiyah; Ikeu Nurhidayah (Universitas Padjadjaran, 2019)
The adolescent with beta-thalassemia major is experiencing both physical and psychological problems, one of them is depression because of suffering a chronic illness. Depression in the adolescent with thalassemia would affect patients’ quality of life and disturb the treatment processes. The purpose of this study was to determine the level of depression in the adolescent with beta-thalassemia major in the Sumedang public hospital. This research was a quantitative descriptive study. The population in this study was adolescents aged 13–20 years with a beta-thalassemia major in the policlinic of Thalassemia in Sumedang Public Hospital. The sample was determined by using total sampling technique, therefore 35 people involved in this study. Data were collected using standard instrument Beck Depression Inventory II. Data were analyzed using frequency distribution. The results of this study showed that adolescent with beta-thalassemia major age 13–20 years in the Sumedang public hospital had 45.7% minimal depression, 20% mild depression, 25.7% moderate depression, and 8.6% severe depression. It can be concluded that the majority of the adolescent with beta-thalassemia major in the hospital have minimal depression and the highest depression type is moderate depression. Nurses were expected to provide psychological services for consultation and periodic depression screening of adolescent with thalassemia.